¬PENGARUH NPL, LDR, CAR, dan BOPO TERHADAP KINERJA PERUSAHAAN (ROA) Studi Kasus Pada Bank Umum Go Public Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2011 – 2013 - Fitiana Arumi, 12.05.51.0023; Sudiyatno, Bambang (Students' Journal of Economic and Management, 2016)
Profitability is a reflection of the financial perfomancein the Corporate Banking. Profitability rate changes will be affect to the investors' decision on investment in the banking company.The purpose of this research is to analyze how the effect of NPL, LDR, CAR, and BOPO to ROA or return on assets of the go public banking company listed on the Indonesia Stock Exchange. This study used samples of companies listed on the Indonesian Stock Exchange. Based on the observations, Period Registered Company in Indonesia Stock Exchange during the period of study between 2011-2013 year is 34 Company for 3 years as many as 98 data. Research data analysis methods using linear regression. The test results showed that the NPL have positive effectand significantly Against ROA ongo public Banking Companies, LDR have no significantly effect against ROA on go public Banking Companies, CAR have no significantly effect against ROA on go public Banking Companies, and BOPO have negative effect and significant  againts ROA of the go public Banking Companies  listed on the Indonesia Stock Exchange.         . Keywords: NPL, LDR, CAR, BOPO, and ROA.